Nutritional evaluation of full-fat soyabean boiled for three time periods - Amos Oladipo, Fanimo (Universiti Putra Malaysia Press, 1996)
The nutritional value of full-fat soyabean (FFSB) boiled for three time periods (30) 60) 90 min) was studied in a balanced experiment on rats and a feeding trial with weaner pigs. The crude protein percentage values were 42.34) 42.7) 43.0 and 43.4 for raw) 30) 60 and 90 min boiled soyabean respectively. Ether extract ranged from 12.3% for the raw sample to 19.0% for samples boiled for 90 min. There were slight increases in the amino acid content with increase in processing time while the reverse was the case for the mineral elements and the anti nutritional factors. Protein quality indices showed that feed intake was not influence by boiling. The protein efficiency ratio (PER) and net protein retention (NPR) values decreased with increasing boiling time. Weight gain and feed/gain of pigs were improved (P < 0.05) with boiling time) while boiling had no significant effect on feed intake. Increasing boiling time tends to improve the nutritive value of FFSB slightly.